European veterinary public health specialization: Post-graduate training and expectations of potential employers - Alonso, Silvia; Darr, S.; Fahrion, Anna S.; Harisberger, M.; Papadopoulou, C.; Zimmerli, U. (University of Toronto, 2013)
Residents of the European College of Veterinary Public Health (ECVPH) carried out a survey to explore the expectations and needs of potential employers of ECVPH diplomates and to assess the extent to which the ECVPH post-graduate training program meets those requirements. An online questionnaire was sent to 707 individuals working for universities, government organizations, and private companies active in the field of public health in 16 countries. Details on the structure and activities of the participants' organizations, their current knowledge of the ECVPH, and potential interest in employing veterinary public health (VPH) experts or hosting internships were collected. Participants were requested to rate 22 relevant competencies according to their importance for VPH professionals exiting the ECVPH training. A total of 138 completed questionnaires were included in the analysis. While generic skills such as “problem solving” and “broad horizon and inter-/multidisciplinary thinking” were consistently given high grades by all participants, the importance ascribed to more specialized skills was less homogeneous. The current ECVPH training more closely complies with the profile sought in academia, which may partly explain the lower employment rate of residents and diplomates within government and industry sectors. The study revealed a lack of awareness of the ECVPH among public health institutions and demonstrated the need for greater promotion of this veterinary specialization within Europe, both in terms of its training capacity and the professional skill-set of its diplomates. This study provides input for a critical revision of the ECVPH curriculum and the design of post-graduate training programs in VPH.